Influence Factor Social and Economy to Productivity Oil Palm Plantation Self-Reliance in Subdistrict Mersam Regency Batanghari-Indonesia - Nainggolan, Viona; Rihi, Micha Snoverson Ratu; Nainggolan, Saidin (RIRAI Publisher, 2025)
This study aims to: analyze the influence of social and economic factors on the productivity of Self-Help Palm Oil in Mersam District. The analysis method in the study used the Partial Least Square (PLS) approach with 62 respondents. The results of the study showed 1) Oil palm farming is carried out conventionally. The average area of oil palm land is 3.4065 ha per farmer. The number of oil palm trees depends on the planting pattern. Spraying and fertilization are carried out twice a year. The average age of oil palm is 4 - 21 years. Farming activities are carried out by family and non-family labor. The process harvesting done 2 time in a month. 2) Factor social in the form of age in research area that is 32 – 72 year. Flat- flat amount liability family farmer is 0 – 6 people, the majority of farmers' ethnic groups are Javanese, Batak and Malay, the motivation of farmers is in the high category and the level of cosmopolitanism of farmers is good. In the economic factor in the form of access to marketing where farmers sell their production to middlemen, loading, and factories, oil palm farmers sell TBS at a price of Rp. 1900 - 2,100, the largest capital which are issued is Rp. 160,377,000 and distance travel around 15.4 – 20.4 km. 3) Social factors have a direct positive effect on productivity. Social factors influential negative to productivity through variable moderation use of production inputs. Economic factors have a direct positive and significant effect on productivity. Economic factors have a positive and significant effect on productivity through the moderating variable of use of production inputs.